La nuit américaine dans Noir de Robert Coover - Marc Amfreville (Anglophonia)
Robert Coover’s yet unpublished (in its original English version at least) latest novel Noir forces its reader by addressing him/her directly to acknowledge and deconstruct various clichés of the City. Drawing from recognizable romances and tales of detection (early English, American and Victorian Gothic), but also from classic writers such as Hawthorne and Conrad, not to mention Chandler and the film adaptation of The Big Sleep, Coover takes us into an urban nightmare in its horizontal labyrinthine dimension and its vertical and spectral depths. Under the highly erotic and conventionally threatening figure of a Black widow, who owes much to Baudelaire’s death ringing passer-by, and by resorting extensively to the poetics of erasure, veiling and claustration, this highly metatextual novel captures in its spider’s web the simulacrum of all detective fiction by pitting it against the anticipated shadow presence of the most ambitious critique (Benjamin, Derrida, Baudrillard).